1973
DOI: 10.1007/bf02389116
|View full text |Cite
|
Sign up to set email alerts
|

Orthodox semigroups whose idempotents satisfy a certain identity

Abstract: An orthodox semigroup S is called a left [right] inverse semigroup if the set of idempotents of S satisfies the identity xyx = xy [xyx = yx].Bisimple left [right] inverse semigroups have been studied by Venkatesan [6].In this paper, we clarify the structure of general left [right] inverse semigroups.Further, we also investigate the structure of orthodox semigroups whose idempotents satisfy the identity xyxzx = xyzx.In particular, it is shown that the set of idempotents of an orthodox semigroup S satisfies x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…By [12], η 1 is a congruence on S and S/η 1 is a left inverse semigroup. Dually, a relation η 2 on S is defined by aη 2 b if and only if…”
Section: Structure Of Lr-c Semigroupsmentioning
confidence: 97%
See 2 more Smart Citations
“…By [12], η 1 is a congruence on S and S/η 1 is a left inverse semigroup. Dually, a relation η 2 on S is defined by aη 2 b if and only if…”
Section: Structure Of Lr-c Semigroupsmentioning
confidence: 97%
“…By [12], S is isomorphic to a subdirect product of S/η 1 and S/η 2 where the isomorphism φ : S −→ S/η 1 × S/η 2 is given by aφ = (ã,ã), a ∈ S whereã,ã denote the η 1 -class and η 2 -class containing a, respectively. Let ψ : S/η 1 −→ S/σ and ξ : S/η 2 −→ S/σ be defined byãψ =ā andãξ =ā, whereā is the σ-class containing a.…”
Section: Theorem 17 a Quasi-inverse Semigroup Is Isomorphic To A Spinmentioning
confidence: 99%
See 1 more Smart Citation
“…
This is a continuation and also a supplement of the previous papers [5], [6] and [8] concerning orthodox semigroupsllIn [8], it has been shown that a quasi-inverse semigroup is isomorphic to a subdirect product of a left inverse semigroup and a right inverse semigroup.In this paper, we present a structure theorem for quasi-inverse semigroups and some relevant matters. e e E, define Seas follows: fse= efe, fs E. Then, (fh)8 e = efhe = efehe = (efe) (ehe) = (f6e) (h~ e) for f,h eE (since E is a regular band).
…”
mentioning
confidence: 90%
“…In [8], it has been shown that a quasi-inverse semigroup is isomorphic to a subdirect product of a left inverse semigroup and a right inverse semigroup.…”
mentioning
confidence: 99%